2012
DOI: 10.1111/j.1469-8137.2011.04037.x
|View full text |Cite
|
Sign up to set email alerts
|

From climate change to molecular response: redox proteomics of ozone‐induced responses in soybean

Abstract: Summary• Ozone (O 3 ) causes significant agricultural losses, with soybean (Glycine max) being highly sensitive to this oxidant. Here we assess the effect of elevated seasonal O 3 exposure on the total and redox proteomes of soybean.• To understand the molecular responses to O 3 exposure, soybean grown at the Soybean Free Air Concentration Enrichment facility under ambient (37 ppb), moderate (58 ppb), and high (116 ppb) O 3 concentrations was examined by redox-sensitive thiol labeling, mass spectrometry, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 62 publications
(236 reference statements)
4
25
1
Order By: Relevance
“…A recent proteomics experiment investigating the timing of changes in thylakoid proteins to O 3 exposure showed decreased abundance of most proteins within 14 d of exposure to O 3 (Bohler et al, 2011), consistent with the transcriptional changes reported here. Previous work at this site also demonstrated that oxidation of Rubisco protein was significantly greater in plants exposed to elevated [O 3 ] (Galant et al, 2012). In this study, the decrease in photosynthetic metabolism fed forward to alter leaf contents of sugars, sugar alcohols, and starch.…”
Section: O 3 Decreases Metabolites Associated With Primary Metabolismsupporting
confidence: 49%
“…A recent proteomics experiment investigating the timing of changes in thylakoid proteins to O 3 exposure showed decreased abundance of most proteins within 14 d of exposure to O 3 (Bohler et al, 2011), consistent with the transcriptional changes reported here. Previous work at this site also demonstrated that oxidation of Rubisco protein was significantly greater in plants exposed to elevated [O 3 ] (Galant et al, 2012). In this study, the decrease in photosynthetic metabolism fed forward to alter leaf contents of sugars, sugar alcohols, and starch.…”
Section: O 3 Decreases Metabolites Associated With Primary Metabolismsupporting
confidence: 49%
“…To date, no information is available regarding ozone-induced changes in the S-nitroso-proteome of plants. Although several studies describe the impact of acute ozone exposure on total proteomes of rice, soybean, wheat, and poplar [29][32], the issue of redox-linked protein modifications upon ozone has only been examined in two studies [33], [34]. Ozone exerts bi-functional effects on earth.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is estimated that by 2020 current day, the yield losses due to O 3 damage will rise from current 13% and 23%, to 16% and 35%, respectively for cereals and soybean productions of China [3], [4]. Economically, annual crop losses induced by O 3 are estimated at $3–5.5 billion in China, and will likely increase by 16%–110% in the near future [5], [6]. These predictions suggest that China in particular might be on the cusp of substantial reductions in grain production following the rapid economic transformation, industrialization and urbanization [7].…”
Section: Introductionmentioning
confidence: 99%